Developing Infographics of Cakeapp-Based Teaching Speaking Ideas for 11th Grade Tourism Vocational School English Teacher at SMK Negeri 2 Tabanan - Sitangsu, Ni Luh Manik Santi Devi; Utami, IGA Lokita Purnamika; Agustini, Dewa Ayu Eka (PROJECT (Professional Journal of English Education), 2025)
The integration of digital tools in teaching speaking skills has become essential in modern education, particularly in vocational schools in Indonesia. However, many English teachers in vocational schools, especially those in tourism, face challenges in utilizing advanced digital tools like CakeApp due to limited resources and inadequate training. This research aims to develop and evaluate CakeApp-based teaching infographics tailored for 11th-grade English teachers in the tourism sector at SMK Negeri 2 Tabanan. By employing the Design and Development (D&D) model, specifically the DDE framework, the research focuses on designing infographics that support speaking activities using CakeApp’s interactive features. The development process consists of needs analysis, content creation, and expert evaluations. The study shows that the developed infographics align with curriculum objectives and improve the teachers’ ability to deliver engaging speaking lessons. The quality evaluation results indicate that the infographics are of excellent quality, with high expert judgment scores and positive user feedback. This research contributes to the integration of digital tools in vocational education, enhancing speaking skills in a contextual and interactive manner.